Acute Perforated Appendicitis: Clinical Profile and Analysis of Risk Factors - Kidwai, Roman; Sharma, Anup (Journal of Nepalgunj Medical College, 2018)
Introduction: The incidence of complicated acute appendicitis, including perforated or gangrenous appendicitis, remains considerably high (28-29%) despite the availability of modern imaging. Acute perforated appendicitis is associated with increased postoperative morbidity and mortality. The aim of the study was to analyze the clinico-pathological profile and outcomes for suspected perforated acute appendicitis and to determine the factors influencing the risk of perforated appendicitis. Materials and Methods: This was a prospective observational study conducted at Nepalgunj Medical College and Teaching Hospital from November 2016 to August 2018. Patients with suspected appendicle perforation were included. The diagnosis was confirmed atlaparotomy. History, physical findings, biochemical and radiological findings were noted. Results: There were 74 patients. The maximum number of patients were in the age group of 0-20 and 21-40 years with a male dominance (M:F 1.9:1). The common presenting features were pain starting in right iliac fossa and becoming generalized with features of peritonitis. Majority presented late to the hospital with the mean duration of 6.35±2.46 days. 17 (22.97%) patients had deranged renal function test at presentation. All patients underwent laparotomy and appendicectomy. The commonest site of perforation was the tip of appendix (58.08%). 27(52.94%) had generalized purulent peritonitis. All had features of acute appendicitis on histological examination. Of the 75 patients only 17 (22.97%) patients had fecolith. 21 (28.37%) had postoperative complications, commonest being surgical site infection (25.67%). Five (6.67%) patients died after surgery. The common cause of death was septic shock with multiorgan failure. Only one patient died due to myocardial infarction. The complications and mortality were common in those patients whose presentation was late i. e after 72 hours from the onset of symptoms, whose renal function was deranged, age > 60, and who had pyoperitoneum. CONCLUSION: Acute perforated appendix is not uncommon. Males are more common with younger people commonly getting affected. Delayed presentation, pyoperitoneum, age >60 are the common risk factors associated with morbidity and mortality.